Persepsi Mahasiswa Tentang Demokrasi di Kota Maumere - Alfian Harbiyanto (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine student perceptions of democracy in the city of Maumere. The research method used in this study is qualitative in the form of case study research through data collection techniques, participant observation techniques, interviews and documentation. The findings of this study are: First, the implementation of democracy in various aspects of the Maumere community, namely the implementation of civil liberty rules, the implementation of political rights for every community and the development of democratic institutions (institutional democracy) in government and society. civil. Second The condition of civil society freedom in Maumere can be seen from the relatively high level of freedom of association and assembly of civil society organizations, civil society organizations that appear in every social structure of society. The three factors that influence democracy in Maumere consist of: community welfare factors, social and political factors, civic culture and historical roots.